Density functional theory studies of transition metal carbides and nitrides as electrocatalysts. (28th September 2021) - Tian, Dong; Denny, Steven R.; Li, Kongzhai; Wang, Hua; Kattel, Shyam; Chen, Jingguang G.
Abstract : This review summarizes density functional theory (DFT) studies of TMCs and TMNs as electrocatalysts. It provides atomistic details of HER, OER, ORR, N2 RR and CO2 RR and also presents a future outlook in designing TMCs and TMNs based electrocatalysts. Abstract : Transition metal carbides and nitrides are interesting non-precious materials that have been shown to replace or reduce the loading of precious metals for catalyzing several important electrochemical reactions. The purpose of this review is to summarize density functional theory (DFT) studies, describe reaction pathways, identify activity and selectivity descriptors, and present a future outlook in designing carbide and nitride catalysts for the hydrogen evolution reaction (HER), oxygen evolution reaction (OER), oxygen reduction reaction (ORR), nitrogen reduction reaction (N2 RR), CO2 reduction reaction (CO2 RR) and alcohol oxidation reactions. This topic is of high interest to scientific communities working in the field of electrocatalysis and this review should provide theoretical guidance for the rational design of improved carbide and nitride electrocatalysts.